Noise characteristics with CMOS sensor array scaling. (February 2020) - Accarino, Claudio; Annese, Valerio F.; Cheah, Boon Chong; Al-Rawhani, Mohammed A.; Shah, Yash D.; Beeley, James; Giagkoulovitis, Christos; Mitra, Srinjoy; Cumming, David R.S.
Highlights: A sensor array performs better than a standalone sensor with the same area independently by the type of the sensor. A defined signal standard deviation can be achieved by tuning the number of sensors embedded into a sensor array. Optimization strategy for simultaneous multiple sensing on a sensor array. Abstract: An important consideration when scaling semiconductor sensor devices is the effect it may have on noise performance. Overall signal to noise ratio can be improved both by increasing sensor size, or alternatively by averaging the signal from two or more smaller sensors. In the design of sensor systems it is not immediately clear which is the best strategy to pursue. In this paper, we present a detailed theoretical and experimental study based on three different sensor arrays that show that an array of small independent sensors is always less noisy than a large sensor of the same size.